2009
DOI: 10.1103/physrevb.79.193311
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of photoexcited carriers by resonant tunneling through a single quantum dot

Abstract: We show that the resonant tunnel current through a single energy level of an individual quantum dot within an ensemble of dots is strongly sensitive to photoexcited holes that become bound in the close vicinity of the dot. The presence of these holes lowers the electrostatic energy of the quantum dot state and switches the current carrying channel from fully open to fully closed with a high on/off ratio (> 50). The device can be reset by means of a bias voltage pulse. These properties are of interest for charg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…By incorporating various combinations and compositions of potential barriers, quantum wells, and/or quantum dot layers into the intrinsic region of the device, it has proved possible to fine tune the carrier dynamics, capture and recombination processes, and to exploit tunneling and confinement effects for applications in photonic and quantum information processing. For example, p-i-n diodes have been used as single photon emitters [4], and as sensitive photodetectors in which a single photoexcited carrier localized in a quantum well or at a quantum dot can produce a significant change in the conductance of the device [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating various combinations and compositions of potential barriers, quantum wells, and/or quantum dot layers into the intrinsic region of the device, it has proved possible to fine tune the carrier dynamics, capture and recombination processes, and to exploit tunneling and confinement effects for applications in photonic and quantum information processing. For example, p-i-n diodes have been used as single photon emitters [4], and as sensitive photodetectors in which a single photoexcited carrier localized in a quantum well or at a quantum dot can produce a significant change in the conductance of the device [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that embedding the QD layer between the tunnel barriers can improve the multiplication factor; the schematic of this device structure is shown in Figure 1 . For the coulomb potential energy of quantum dot to be greatly changed by nearby localized charge than quantum well, a much higher level of sensitivity (> 1,000%) and a means of opening/closing the current channel with a very high on/off ratio (> 50) were provided [ 5 ]. This structure expands prospects to further improve the performances of QD-RTD for charge-sensitive photon-counting detectors.…”
Section: Introductionmentioning
confidence: 99%
“…When the upper surface of the diode is illuminated uniformly with unfocused laser light of increasing intensity, the QD resonant peaks shift steadily towards lower bias [16]. However, the shapes, amplitudes, and relative bias positions of the peaks remain approximately the same.…”
mentioning
confidence: 95%
“…1(b)]. This jitter is attributed to slow fluctuations in current paths between the contact layers and barrier and it can be eliminated by making fast (< 0:1 s) sweeps of IðVÞ [16]. However, with the low power (2 fW) scanned and focused laser beam, the data remain noise-free [ Fig.…”
mentioning
confidence: 99%